The difference in radiopacity of microhybrid, nanofiller and nanohybrid composite resins with conventional periapical radiographic techniques: Perbedaan radiopasitas resin komposit microhybrid, nanofiller dan nanohybrid dengan teknik radiografi periapikal konvensional - Dava Karunia Akbar; Sarianoferni; Emy Khoironi (Makassar Dental Journal PDGI Makassar, 2021)
Objective: The radiopacity of dental composite restorative materials is important since it allows assessment of the integrity of composite restorations, accurate diagnosis of secondary caries development and evaluation of the interface between the com-posite restorative material and the tooth structure on the new materials introduced in the market nowadays. The purpose of this observation is to determine the differences of microhybrid, nanofiller and nanohybrid composite resins on their radiopacity using conventional periapical radiography techniques. Methods: Composite resins samples were divided into three groups; 30 samples each. Group I were microhybrid composite resin. Group II were nanofiller composite resin. Group III were nanohybrid composite resin. Each specimen was placed on a dental film and exposed using conventional radiographic techniques with the specification of 70 kVp, 8mA and 0.25s, then processed using instant film procedures. Observations were carried out using the densitometer. The results of calculations were analyzed by using the one way Anova test. Results: Significant radiopacity dif-ferences were occurred in those three groups (p<0.05). Nanohybrid composite resin (2.32 mmAl) was significantly more ra-diopaque than microhybrid composite resin (2.20 mmAl) and nanofiller composite resin (2.10 mmAl). Conclusion: There are differences between microhybrid, nanofiller and nanohybrid composite resins. Resins that have the highest to the lowest ra-diopacity levels are nanohybrid, microhybrid, and nanofiller composite resin.